2016
DOI: 10.1007/s00382-016-3219-z
|View full text |Cite
|
Sign up to set email alerts
|

Tropical intraseasonal oscillation simulated in an AMIP-type experiment by NICAM

Abstract: and northward propagation, during summer. The overall shape of the seasonal cycle as measured by the numbers of significant MJO and BSISO days in a month is relatively well captured. Two major biases, however, are also identified. The amplitude of the simulated ISO is weaker by a factor of ~2. Significant BSISO events sometimes appear even during winter (December-April), amounting to ~30 % of the total significant ISO days as opposed to ~2 % in the observation. The results here warrant further studies using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 94 publications
1
20
0
Order By: Relevance
“…Meanwhile, in the suppressed to preconditioning phases of the MJO, the horizontal transport of moisture by the high-frequency variability played an important role in moistening the lower to middle troposphere. The above considerations imply that the relatively weak convective signal associated with the MJO in the NICAM simulations (Nasuno 2013;Kodama et al 2015;Kikuchi et al 2017a) can be related to the overdevelopment of the grid-scale convection in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in the suppressed to preconditioning phases of the MJO, the horizontal transport of moisture by the high-frequency variability played an important role in moistening the lower to middle troposphere. The above considerations imply that the relatively weak convective signal associated with the MJO in the NICAM simulations (Nasuno 2013;Kodama et al 2015;Kikuchi et al 2017a) can be related to the overdevelopment of the grid-scale convection in the model.…”
Section: Discussionmentioning
confidence: 99%
“…The BSISO and MJO PC time series for the models were also obtained in a similar manner by projecting the 25–90‐day filtered simulated OLR onto the observed EEOFs. As discussed by Kikuchi et al (), since we are interested in how models are able to accurately simulate the observed spatiotemporal structures of the ISO rather than in isolating the model's preferred spatiotemporal structures of the ISO, we do not use EEOFs derived from model simulations. Because the ISO simulated in the models is usually much weaker in amplitude, the PCs in the models are adjusted by dividing by α, normalα=truePCMJOmodel¯+truePCBSISOmodel¯truePCMJOobs¯+truePCBSISOobs¯, before determining the ISO mode for a given day.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Noda et al 2010Noda et al , 2012Pauluis and Garner 2006). Present and future climate simulations using 14-km mesh NICAM were performed (Kodama et al 2015;Satoh et al 2015) and analyzed in terms of intraseasonal variation (Kikuchi et al 2017), tropical synoptic-scale disturbance (Fukutomi et al 2015), tropical cyclones (Satoh et al 2015;Yamada et al 2017), and climate sensitivity (Chen et al 2016). The performance of MJO prediction was statistically confirmed through 14-km mesh, 54-ensemble simulation (Miyakawa et al 2014).…”
Section: Jamstec Model Intercomparision Projectmentioning
confidence: 96%